2017
DOI: 10.1371/journal.pone.0174593
|View full text |Cite
|
Sign up to set email alerts
|

Video-urodynamic characteristics of non-neurogenic, idiopathic underactive bladder in men – A comparison of men with normal tracing and bladder outlet obstruction

Abstract: ObjectiveUnderactive bladder is frequently encountered in elderly patients. It may result from detrusor underactivity (DU) or low detrusor contractility due to a urethral sphincter inhibitory effect. This study analyzed the video-urodynamic study (VUDS) characteristics of patients with underactive bladder in a large cohort of men with lower urinary tract symptoms (LUTS).MethodsMale patients with LUTS who had failed the initial treatment were consecutively enrolled. All patients underwent detailed urological in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 22 publications
0
22
0
1
Order By: Relevance
“…The prevalence rates were 12-20% [87,89,90] and 17.6% [4] in male and female non-neurogenic VD refractory to medication patients, respectively. The incidence increased in young males [89] in patients with bladder pain syndrome [88] and in idiopathic DU patients [91]. Sphincteric BoNT-A injections might provide chemo-denervation of the EUS by inhibition of acetylcholine release in the neuromuscular junction to relieve the USD in PRES [23].…”
Section: Urethral Sphincter Bont-a Injections In Patients With Poor Rmentioning
confidence: 99%
“…The prevalence rates were 12-20% [87,89,90] and 17.6% [4] in male and female non-neurogenic VD refractory to medication patients, respectively. The incidence increased in young males [89] in patients with bladder pain syndrome [88] and in idiopathic DU patients [91]. Sphincteric BoNT-A injections might provide chemo-denervation of the EUS by inhibition of acetylcholine release in the neuromuscular junction to relieve the USD in PRES [23].…”
Section: Urethral Sphincter Bont-a Injections In Patients With Poor Rmentioning
confidence: 99%
“…Voiding dysfunction may result from detrusor underactivity (DU), bladder outlet obstruction (BOO), urethral sphincter hyperactivity, or poor relaxation of the external urethral sphincter (PRES) during micturition. A previous urodynamic study reported DU in 12.4% of men [1] and in 23.1% of women [2] with voiding lower urinary tract symptoms (LUTS). Urethral sphincter hyperactivity was noted in 17.0% of women [3], and PRES in 39.5% of men [1] and 17.6% of women [3] with voiding dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Repeated uroflows with EMG and postvoid residual urines are needed to verify the diagnosis in children . In adults, symptoms and noninvasive evaluation alone may not be able to diagnose or differentiate DV from other causes of VD . Although voiding symptoms or even urinary retention may be expected in DV patients, storage symptoms, usually due to detrusor overactivity, can be quite common and a significant proportion of patients present with mixed LUTS …”
Section: How Well Do We Understand and Diagnose DV In Children And Admentioning
confidence: 99%
“…12 Whatever the muscle involved that increases urethral resistance, it would lower the urine flow rate. Such variability of definition may explain the wide prevalence range reported among men (14%-43%) [13][14][15][16] and women with lower urinary tract symptoms (LUTS) (10.5%-34.6%). 12,17,18 Other researchers report a much lower prevalence of "learned VD" (2% of urodynamic investigations for LUTS in an adult population).…”
Section: And Etiology Of DV In Children and Adultsmentioning
confidence: 99%
See 1 more Smart Citation